Exploring new approach to make rare earth doped optical fibre - Foo, Pee Chun (2015)
In this paper we explore on an alternative technique to make rare earth (RE) doped optical fibre and their advantages over the conventional modified chemical vapour deposition (MCVD) process in combination with solution doping and powder sinter technology (REPUSIL). One of the existing problem for MCVD process is that the dispersion of RE ions in the preform is not uniform, which leads to clustering of RE ions. The method proposed to resolve or improve this issue is gas-phase deposition technique, which will be discussed largely in this project.